A Analysis of Factors Affecting Waste Using Value Stream Mapping (VSM) On Kaosbekas.Id - Anshori, Mohamad Yusak; Karya, Denis Fidita (Universitas Ciputra Surabaya, 2022)
Abstract: Lean manufacturing approach is a systematic approach which identifies and eliminates waste through continuous improvement: the flow of products that customers want to pursue the perfection. This study aims to determine the amount of waste in Kaosbebas.id and examine the causes of the waste by using Value Stream Mapping (VSM), value stream analysis tools, and fish-bone diagrams. At the beginning of the study, the description of the current state map was carried out for the analysis of the fulfillment of the physical flow and the flow of information on the production of Kaosbebas.id. After weighting the waste, the researchers distributed questionnaires to informants related to the custom T-shirt production process to obtain the results of identifying the locations of waste and what things made the waste occur during the production process. Furthermore, the researchers conducted an evaluation process so that this waste reduction is expected to increase production efficiency and improve company performance. In addition, this study also aims to provide suggestions for improvements to the manufacture of custom t-shirts during the production process. This study uses a qualitative approach with the methods of observation, interviews, and questionnaires.